Signas Salò: affekt og non-etisk katastrofe - Skjoldager-Nielsen, Kim; Schultz, Laura Luise (Peripeti, 2012)
Deploying the concepts of affect and catastrophe and drawing upon as well an audience survey as statements from the internet and various newspapers, as well as his own experience as an audience member, in this article, Kim Skjoldager-Nielsen unfolds a critical discussion on the learning potential of the performance 'Saló".